In vivo assessment of anticoagulant and antiplatelet effects of Syzygium cumini leaves extract in rabbits - Ahad Abdul Rehman; Azra Riaz; Muhammad Arif Asghar; Muhammad Liaquat Raza; Shadab Ahmed; Kamran Khan (BMC, 2019)
Abstract Background Syzygium cumini (L.) Skeels. is one of the very popular traditionally used medicinal plants with numerous pharmacological activities including antioxidant, hypoglycemic and anti-inflammatory. However, actions of S. cumini on blood coagulation and other parameters of blood were poorly pharmacologically studied. Therefore, aim of this present investigation is to examine the effects of methanolic extract of S. cumini on blood coagulation and anticoagulation factors in healthy white albino rabbits at different doses. Methods Blood samples were drawn twice during this study and biochemical assays were performed to determine the effect on different parameters such as coagulation, anticoagulation, hematological, Protein C (PC) and thrombin antithrombin (TAT) complex and platelet aggregation. Results The results showed significant increase in RBCs, hemoglobin, hematocrit and platelets counts up to 1.4 × 103/cm, 2.2 g/dl, 6%, 248.2 × 103/cm respectively. While, thrombin and bleeding time were also prolonged in dose dependent manner which is highly significant (p ≤ 0.005) as compared to control. Similarly, highly significantly increased (p ≤ 0.005) in levels of protein C, thrombin antithrombin complex at dose of 500 mg/kg were observed. Whereas, levels of platelets aggregation and fibrinogen were decreased at high doses. Conclusion The obtained findings of hematological and coagulation tests concludes possibly S. cumini possess anticoagulant and antiplatelet effects.